A systematic review of antiproton radiotherapy - Bittner, Martin-Immanuel; Grosu, Anca-Ligia; Wiedenmann, Nicole; Wilkens, Jan J. (Frontiers in Physics, 2014)
Antiprotons have been proposed as possible particles for radiotherapy; over the past years, the renewed interest in the potential biomedical relevance led to an increased research activity. It is the aim of this review to deliver a comprehensive overview regarding the evidence accumulated so far, analysing the background and depicting the current status of antiprotons in radiotherapy. A literature search has been conducted, including major scientific and commercial databases. All articles and a number of relevant conference abstracts published in the respective field have been included in this systematic review. The physical basis of antiproton radiotherapy is complex; however, the characterisation of the energy deposition profile supports its potential use in radiotherapy. Also the dosimetry improved considerably over the past few years. Regarding the biological properties, data on the effects on cells are presented; however, definite conclusions regarding the relative biological effectiveness cannot be made at the moment and radiobiological evidence of enhanced effectiveness remains scarce. In addition, there is new evidence supporting the potential imaging properties, for example for online dose verification. Clinical settings which might profit from the use of antiprotons have been further tracked. Judging from the evidence available so far, clinical constellations requiring optimal sparing in the entrance region of the beam and re-irradiations might profit most from antiproton radiotherapy. While several open questions remain to be answered, first steps towards a thorough characterisation of this interesting modality have been made.